A adaptação ao câncer em casais brasileiros - Delfino, Julia Luana (Universidade Federal de São Carlos, 2023)
Caregivers are of fundamental importance in assisting people being treated for cancer. When the primary caregiver is the patient’s spouse, however, cancer becomes a shared stressor that is faced by both members of the couple. Considering the limited number of studies on the psychological effects of cancer for couples, and the importance of this issue, the aim of the current study was to describe individual and dyadic coping strategies used by Brazilian couples living with cancer, and their perceptions of individual well-being and of the marital relationship. For this purpose, 20 participants were recruited, 12 cancer patients and 8 caregiver-partners, who responded to instruments to assess their use of emotional regulation strategies and dyadic coping, as well as their perceptions of quality of life and marital satisfaction. Compared to the caregiver-partners, cancer patients reported significantly greater use of three emotional regulation strategies (functional forms of emotional regulation, avoidance of passivity, and control of pessimism), but similar perceptions of their use of dyadic coping strategies, quality of life and marital satisfaction. Only perceptions of emotional well-being were different, and, unexpectedly, were more positive for patients than for caregivers. The use of functional forms of emotional regulation, avoidance of passivity, and control of pessimism were significantly related to perceptions of quality of life. Control over externalizing aggression and all forms of dyadic coping were related to satisfaction with the marital relationship. In the patients’ comments, most indicated the importance of practical and emotional support received from their partners. The number of responses was low, but the caregivers described emotional difficulties that they had not shared with others. The results indicate the importance of emotion regulation strategies for the well-being of the patients and caregivers, and the importance of control over aggressiveness and dyadic coping skills for the quality of the couple relationship. In future studies, it will be important to pay attention to the needs of both members of the couple, and to develop and evaluate interventions to strengthen abilities that contribute to the quality of the conjugal relationship, considering the centrality of this relationship in the lives of patients and caregiver partners.
Adaptation to cancer among Brazilian couples
Keywords: Parceiros íntimos; Apoio psicológico; Psicooncologia; Psycho-oncology; Intimate partners; Psychological support; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA